Clinical Holistic Medicine: Induction of Spontaneous Remission of Cancer by Recovery of the Human Character and the Purpose of Life (the Life Mission) - Søren Ventegodt; Mohammed Morad; Eytan Hyam; Joav Merrick (The Scientific World Journal)
The recovery of the human character and purpose of life with consciousness-based medicine seems to be able to induce spontaneous remissions in several diseases. On two different occasions, we observed breast tumors reduced to less than half their original diameters (clinically judged) during a holistic session, when working with the patients in accordance with the holistic process theory of healing, the life mission theory, and the theory of human character. One tumor was histologically diagnosed as malign breast cancer prior to the session, while the other was under examination. As both patients had the affected regions of the breast surgically removed immediately after the session, we are unable to determine if they were actually healed by the holistic treatment. We find it extremely interesting that the size of a tumor can be reduced dramatically within a few hours of holistic treatment, when the patient is highly motivated for personal development. The reduction of tumor size is in accordance with the holistic view that many types of cancer are caused by emotional and existential disturbances. From a holistic perspective, cancer can be understood as a simple disturbance of the cells, arising from the tissue holding on to a trauma with strong emotional content. This is called “a blockage”, where the function of the cells is changed from their original function in the tissue to a function of holding emotions. The reduction of the tumor in the two cases happened when old painful emotions were identified in the tissues, in and around the tumor, and processed into understanding; when the patients finally did let go of negative beliefs and attitudes that had kept the feeling(s) repressed to that part of the body, the tumor first softened and then disappeared, presumably by apoptosis. We believe that the consciousness-based/holistic medical toolbox has a serious additional offer to cancer patients, and we will therefore strongly encourage the scientific society to explore these new possibilities. Our holistic medical research meets both ethical dilemmas and practical difficulties, as it obviously is important for the research in induced spontaneous remissions that surgery and chemotherapy is not used before it is absolutely necessary. On the other hand, is it important for the patient's survival that they receive any well-documented treatment as soon as possible. An additional aspect for the patient who is able to cure her own cancer is that she is much less likely to get cancer again and much better prepared to deal with other diseases and challenges in life. Knowing that one can fight even cancer gives a strong belief in life and the need to improve quality of life. The high incidence of secondary cancers and the physical and emotional wounds from the biomedical treatment seem to justify a focus on prevention and additional holistic treatment modules. To support the patient in learning the mastery of coherence of body and life, using the crisis of cancer to recover the human character and the purpose of life, seems turning a personal potential disaster into the greatest gift of all. When it comes down to it, life is not just about surviving; what is more important is to live fully, to learn from the great challenges of life, and to obtain the optimal quality of life while being here.